2020
DOI: 10.1002/cpp.2440
|View full text |Cite
|
Sign up to set email alerts
|

How thinking hurts: Rumination, worry, and avoidance processes in adjustment to bereavement

Abstract: Repetitive negative thought plays an important role in the maintenance of mental health problems following bereavement. To date, bereavement researchers have primarily focused on rumination (i.e., repetitive thought about negative events and/or negative emotions), yet the interest in worry (i.e., repetitive thought about uncertain future events) is increasing. Both cognitive processes potentially lead to poorer adaptation to bereavement by contributing to loss‐related avoidance and behavioural avoidance of act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 62 publications
4
34
0
Order By: Relevance
“…This result is consistent with the proposal that rumination and worry may lead to loneliness. The mechanisms tend to be a strain in close relationships, promote an inward focus leading to less engagement in other people and outward tasks, and encourage behavioral inactivity that hinders access to corrective experiences ( 21 23 ). Future studies should assess whether rumination and worry create loneliness, whether loneliness creates rumination and worry, or whether the relationship is reciprocal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result is consistent with the proposal that rumination and worry may lead to loneliness. The mechanisms tend to be a strain in close relationships, promote an inward focus leading to less engagement in other people and outward tasks, and encourage behavioral inactivity that hinders access to corrective experiences ( 21 23 ). Future studies should assess whether rumination and worry create loneliness, whether loneliness creates rumination and worry, or whether the relationship is reciprocal.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, individuals brooding about their loneliness may lead to the conclusion that seeking contact will fail. Worry increases appraisals of the probability and cost of negative outcomes of future events (e.g., “They will reject me,”) ( 23 ). Both of these internal activities may provide reasons for behavioral withdrawal, leading to less access to experiences that could disconfirm the very thoughts strengthened by rumination and worry.…”
Section: Introductionmentioning
confidence: 99%
“…This result is consistent with the proposal that rumination and worry may lead to loneliness. The mechanisms tend to be a strain in close relationships, promote an inward focus leading to less engagement in other people and outward tasks, and encourage behavioral inactivity that hinders access to corrective experiences (21)(22)(23). Future studies should assess whether rumination and worry create loneliness, whether loneliness creates rumination and worry, or whether the relationship is reciprocal.…”
Section: Discussionmentioning
confidence: 99%
“…Borkovec et al, 1998). Indeed, worry predicts worsening of prolonged grief symptoms over time (Eisma et al, 2017), and cognitive avoidance has been shown to partially mediate the relationship between worry and prolonged grief symptoms (Eisma et al, 2020a).…”
Section: Introductionmentioning
confidence: 99%